Characterization of the Sugar Utilization Gene polS from Ralstonia solanacearum - Duangkhae Kanjanasopa; Orawan Chatchawankanphanich; Srimek Chowpongpang; Wichai Kositratana; Niphone Thaveechai (Agriculture and Natural Resources, 2006)
The gene coding for sorbitol dehydrogenase (polS) from Ralstonia solanacearum strain TO 264 biovar 3 was cloned, sequenced, and compared to homologous sequences from the other bacteria. The result showed that the sorbitol dehydrogenase gene from R. solanacearum strain TO264 displayed the highest similarity to that of R. solanacearum GMI1000 with 99.6% amino acid similarity and the least similarity to sequence of Pseudomonas syringae pv. syringae with 56% amino acid similarity. Phylogenetic analysis of polS showed the Burkholderia cepacia sequence to join as sister to the R. solanacearum TO264 pair. Analysis of the deduced amino acid sequence revealed homology to enzymes of the short-chain dehydrogenase/reductase protein family. The eight amino acid residues were conserved in most of these proteins. These residues included the almost invariant tyrosine (Y) and lysine (K) residues of consensus sequence Y-X-X-X-K, which were essential for catalysis and were located in the active site in C-terminal whereas the glycine (G) residues of the G-X-X-X-G-X-G segment were characteristic of the NAD+ binding domain in the N-terminal region. The 771 bp of polS gene from R. solanacearum TO264 was subcloned into expression pGEX-2T vector. The polS ORF encoded a protein consisting 256 amino acid residues with estimated molecular mass of 27 kDa by SDS-PAGE analysis.